An integrated approach to the diagnosis of bacterial and fungal bloodstream infections in cancer patients - O. Yu. Kutsevalova; Yu. Yu. Kozel; V. V. Dmitrieva; O. V. Kozuk; I. B. Lysenko (Южно-Российский онкологический журнал, 2020)
Purpose of the study. To evaluate the diagnostic significance of accelerated and affordable verification of a bloodstream infection pathogen using biomarkers: procalcitonin and the Platelia ™ Candida Ag Plus mannan antigen.Patients and methods. 349 cancer patients with febrile fever were examined from 6 medical and diagnostic oncological hospitals in the Southern Federal District of the Russian Federation during 2019. Patients aged from 1 to 85 years were hospitalized in intensive care, pediatric oncology and hematology oncology departments. Patient informed consent for the study wasobtained. The diagnostic algorithm included: a blood test using an automatic BacT /ALERT 3D analyzer and a parallel study of the level of biomarkers with enzyme immunoassay. Identification of strains and determination of sensitivity to antimicrobial agents was determined on a Vitek 2 automatic analyzer (BioMerieux, France). Procalcitonin levels greater than 10 ng/ml were registered to determine the development of bacterial inflammation. Procalcitonin was determined with Procalcitonin — ELISA-BEST kits (Russia). Mannan antigen was determined using Platelia Candida Ag kits (France). The result was considered positive at the antigen concentration of ≥125 pg/ml. Candida mannan antigen allowed us to decide on the involvement of Candida spp. in the infectious process.Results. An integrated approach to the diagnosis of bloodstream infections increased the percentage of detection of pathogens up to 58.7%. Bacterial infection testing both with the blood culture method and the procalcitonin determination in blood serum revealed similar diagnostic values. Candida mannan antigen testing significantly improved the early diagnosis of Candidal infection, despite negative blood culture, which was probably associated with prolonged cultivation of Candida spp. in the blood (from 2 to 5 days). The inclusion of biomarker testing in the diagnostic algorithm in cases of suspected bloodstream infection allowed early pathogen identification and starting an adequate antibacterial or antifungal therapy.Conclusion. An integrated approach to the diagnosis of bloodstream infections improved and, just as importantly, significantly accelerated the pathogen verification. Bacterial infection cases showed comparable results of hemoculturing and biomarker testing; however, in case of candidal infection, determination of Candida mannan antigen appears critical, as it was significantly more sensitive than the result of blood culture and allowed to identify the etiology of fever of unknown origin in many patients.